Triple negative breast cancer: Deciphering the biology and heterogeneity - Uscanga Perales, Grecia Iris; Santuario Facio, Sandra Karina; Ortiz López, Rocío (UANL. Facultad de Medicina, 2016)
Triple negative breast cancer (TNBC) is a subtype of breast cancer (BC) with a heterogeneous nature that stains negatively for estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor 2 (HER2) during immunohistochemistry. Approximately 15---20% of all cases of breast cancer are triple negative phenotypes. Compared to patients with hormone receptor-positive cancer, TNBC patients are typically younger (<50 years), African American, and have a high incidence of mutations in BRCA1/2 genes. To date, not a single targeted therapy has been approved for TNBC treatment, and cytotoxic chemotherapy remains as the standard systemic treatment, meaning that TNBC is an aggressive subtype of breast cancer with a poor prognosis. In this review, the literature search was done up to date on which gene expression profile of TNBC has been analyzed in order to identify the consensus on molecular mechanisms involved in carcinogenesis and/or the prognostic markers of the disease. In conclusion, these studies have reported that TNBC is composed of several clusters or genomic signatures as basal keratins. They have also reported on their proliferation, luminal/basal apocrine, regulatory interferon, immune cells/immunoglobulin related to stem cells, epithelial-mesenchymal, androgen receptor and angiogenesis. However, not all research groups have reported reproducible results. This confirms the heterogeneous nature of TNBC and the need for research on uniform selection criteria. However, these discoveries have led to the proposal of new treatments, such as the addition of platinum salts, new combinations of therapeutic agents, some targeted therapies such as PARP inhibitors, and PI3K and androgen antagonists. There is no doubt that a better understanding of the nature of TNBC will allow individualized and more effective therapies.